A study on mold material and coating effect in sand casting process - Muhammad Fakhri, Zainuddin (2009)
Surface finish is the most desired characteristics to be on product surface. This is because surface finish is a predictor of the performance of a mechanical component, since irregularities in the surface may form nucleation sites for cracks or corrosion. In this study, the impact of mold material and coating on surface finish in sand casting was investigated. By using different kind of material to make the mold and evaluating whether coating give effect to product surface finish, the experiment had been done in 4 different tests by using sand casting process as a method to make the final product. In sand casting process, mold material and coating are two significant concerns, but they have different impact in surface finish. In producing part using sand casting, analyzing test is commonly made between these two features to get good quality surface finish. A result among these two different parameters concerns can be achieved by getting the experiment done which on the other hand, selection of better mold material and use of coating will further provide an improved solution. In this thesis, efforts towards determining good surface finish will be decide using different mold properties and coating. The quality of the surface roughness is determined by using visual and analysis. This Surface Roughness is obtained based on the analyzed using MAHR Perthometer s2. In this present work, the main objective of this study is to analyze the effect of coating between two patterns and decide which one has a better surface finish and to compare mold material whether carbon dioxide, CO2 molding or Greensand molding with and without coating and their effect in product surface finish. The standard design approach is implemented in this experimental study where it only consists of 2 factors at one time which are coating and mold material.2 patterns and 4 final products are produced, whereby the study output is surface roughness, Ra (µm). In this study, MAHR Perthometer s2 is used to measure the surface roughness. The comparison between pattern and product will be analyzed. From the findings, it is shown that that product that used carbon dioxide CO2 as mold material and covered with coating has the best surface finish. Based on the study analysis, it is discovered that using green sand as mold material and not using coating produces poor surface finish while carbon dioxide CO2 with coating produces good surface finish products.